Etnoparenting pada Tradisi Aqiqah di Suku Sasambo Nusa Tenggara Barat - Yuyun Ayu Lestari (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Strengthening parenting practices grounded in local wisdom within the traditions of the Sasambo communities in Nusa Tenggara Barat has become increasingly important amid the homogenizing influence of modern parenting models, while studies that specifically examine ethnoparenting perspectives in the aqiqah tradition across the three ethnic groups (Sasak, Samawa, and Mbojo) remain limited. This study aimed to describe the cultural practices and symbolic meanings of the aqiqah tradition as a form of locally rooted parenting among Sasambo communities. A descriptive qualitative approach was employed with participants comprising traditional leaders and community members from the three Sasambo ethnic groups. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using thematic analysis. The findings reveal differences in terminology and ritual practices in each ethnic group, such as Ngurisang (Sasak), Bekuris (Samawa), and Cafi Sari, Boru, and Dore (Mbojo). Despite these variations in practice, all traditions embody religious, social, and educational values that reinforce cultural identity and child-rearing patterns grounded in local wisdom. The study concludes that the aqiqah tradition in Sasambo communities is not only a religious ritual but also functions as a medium for the internalization of values in parenting. The implications of these findings provide a foundation for developing ethnoparenting models based on local culture in early childhood education.